Bibliometric analysis of global research on cities response to climate change through renewable energy - Dicko, Kagou; Umaru, Emmanuel Tanko; Sanogo, Souleymane; Loewner, Ralf; Okhimamhe, Appollonia Aimiosino (Information Research Communications, 2024)
The intricate connection between energy and urbanisation leads to climate change when inadequately addressed and regrettably, evidence of such has already arisen. As part of the progress towards a sustainable environment, researchers are focusing more on reducing greenhouse gas emissions in cities, which have become major contributors. Meanwhile, renewable energy sources have emerged as a key solution to addressing climate change. This study employed a bibliometric approach to analyze trends in publications and research on the link between climate change and renewable energies from 1992 to 2022, leveraging the Scopus database. The analysis revealed that China, the United States and the United Kingdom were the top contributors in this field. The findings highlighted that China, the U.S. and the U.K. emerged as dominant contributors to this field, with a sharp rise in publication output between 1992 and 2022. This growth was particularly noticeable following the publication of the fourth Intergovernmental Panel on Climate Change Assessment Report in 2007 and the ratification of the Paris Agreement. Furthermore, this study has identified critical areas of focus that relate to renewable energy sources, energy efficiency, energy policy and urban climate change mitigation. This underscores the urgent need to replace fossil fuels with cleaner energy alternatives in cities. Researchers and policy-makers at various levels need to prioritise these areas of research in order to develop effective policies and cut urban greenhouse gas emissions.
Keywords: Bibliometric analysis; Renewable energy; Urban Climate change